2014
DOI: 10.3109/10428194.2013.856007
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor SAHA sensitizes acute myeloid leukemia cells to a combination of nucleoside analogs and the DNA-alkylating agent busulfan

Abstract: Fludarabine (Flu), clofarabine (Clo) and busulfan (Bu) are used in allogeneic hematopoietic stem cell transplant (allo-HSCT). We reported that combining [Flu + Clo + Bu] had a synergistic cytotoxicity in AML cells. We hypothesized that combining [Flu + Clo + Bu] with the histone deacetylase inhibitor SAHA will further enhance cytotoxicity. We exposed the acute myeloid leukemia (AML) cell lines KBM3/Bu2506 and OCI-AML3 to Flu, Clo, Bu and SAHA alone and in various combinations. [Flu + Clo + Bu + SAHA] resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The most important studies are presented in detail in Table 1 [49,[83][84][85][86][87][88][89][90][91], but it should be emphasized that several of these studies are relatively small, describe observations mainly in AML cell lines or used methodological strategies that would not be regarded as optimal today. Thus, knowledge about CDC25 in human AML is in our opinion incomplete, but despite this CDC25 should be regarded as a possible therapeutic target in human AML.…”
Section: Biological Functions Of Cdc25 In Human Amlmentioning
confidence: 99%
“…The most important studies are presented in detail in Table 1 [49,[83][84][85][86][87][88][89][90][91], but it should be emphasized that several of these studies are relatively small, describe observations mainly in AML cell lines or used methodological strategies that would not be regarded as optimal today. Thus, knowledge about CDC25 in human AML is in our opinion incomplete, but despite this CDC25 should be regarded as a possible therapeutic target in human AML.…”
Section: Biological Functions Of Cdc25 In Human Amlmentioning
confidence: 99%
“…We previously showed activation of the DNA-damage response (DDR) in AML and lymphoma cells exposed to combinations of nucleoside analogs, DNA alkylating agents and a histone deacetylase inhibitor [20, 21]. We, therefore, opted to determine whether [Bu+Clo+Flu+Sor] combination also activates DDR in MV-4-11 cells.…”
Section: Resultsmentioning
confidence: 99%
“…These combinations activate DNA damage response, induce histone modifications and lead to cell cycle checkpoint activation and apoptosis [19-21]. A combination of these three drugs also contributes to increased antileukemic efficacy/patient benefit without an apparent concomitant increase in clinical normal-organ toxicity [22].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of CDC25 on AML have been the subject of considerable work in recent years. Song and his colleagues showed that suppressed expression of CDC25A was present in AML cells subsequent to supplementation with antiproliferative as well as cytotoxic agents . Experiments by Madlener and his team suggested that CDC25A deactivation could counteract CCA‐linked proliferation and cytotoxicity .…”
Section: Discussionmentioning
confidence: 99%